Natriuretic peptide referral thresholds and heart failure diagnosis: population-based cohort study. (14th October 2021) - Taylor, C; Ordonez-Mena, J.M; Lay-Flurrie, S; Goyder, C; Jones, N; Roalfe, A; Hobbs, F.D.R
Abstract: Background: Natriuretic peptide (NP) testing is recommended by both the European Society of Cardiology (ESC) and the National Institute for Health and Care Excellence (NICE) for people presenting with symptoms of heart failure (HF) in primary care. However, ESC and NICE guidelines suggest different NP referral thresholds: ESC recommend referral at a lower NP level (BNP≥35pg/ml / NT-proBNP≥125pg/ml) compared to NICE (BNP≥100pg/ml/NT-proBNP≥400pg/ml). Purpose: We aimed to evaluate NP test performance for HF diagnosis for ESC and NICE guideline-defined thresholds. Methods: Population-based cohort study using linked primary and secondary care data from the Clinical Practice Research Datalink in England between 1st January 2000 and 31st December 2018. Participants were adults aged 45 years and above with a NP result: 74, 233 had a BNP and 155, 347 had a NT-proBNP measurement. The main outcome measures were diagnostic performance of NP test (sensitivity, specificity, positive predictive value, negative predictive value) by threshold. Results: A total of 229, 580 patients had a NP test and 21, 102 (9.2%) were diagnosed with HF. The ESC NT-proBNP threshold of 125pg/ml had a sensitivity of 94.6% (94.2 to 95.0) and specificity of 50.0% (49.7 to 50.3) compared to sensitivity of 81.7% (81.0 to 82.3) and specificity of 80.3% (80.0 to 80.5) for the NICE NT-proBNP 400pg/ml threshold. For both guidelines, nearly all patients with a NP level below the threshold did not have HF (negative predictive value ESC 98.9% (98.8 to 99.0) and NICE 97.7% (97.6 to 97.8). Similar performance was found for BNP. Conclusions: The performance of NP testing is dependent on the guideline-specified threshold for referral. In 100 people with HF, using the NICE threshold would falsely reassure 18 patients, whereas the lower ESC threshold would miss just 5 people but twice as many patients would be referred for diagnostic assessment. The optimal NP threshold for referral for HF diagnosis will depend on the healthcare setting. The trade-off between missing HF cases and overwhelming diagnostic services needs to be determined at a national level. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Institute for Health Research